Chicken Manure as a Sustainable Bile Acid Source for Biotechnological Applications - Johannes Holert; Rudolf Wilhelm; Jens Henker; Claudia A. Reinker; Franziska M. Müller; Bodo Philipp (Microbial Biotechnology, 2025)
ABSTRACT Ursodeoxycholic acid (UDCA) is widely administered to dissolve gallstones, treat liver disorders and reduce blood cholesterol levels. This study investigated fresh and dried chicken manure as a sustainable bioresource for chenodeoxycholic acid (CDCA), a precursor for the biotechnological production of UDCA. For this, bile acids from five commercial dried and seven fresh chicken manure samples were analysed. The bile acid pool consisted predominantly of CDCA (30%–90%) and 7‐keto lithocholic acid (7k‐LCA, 8%–56%), with minor amounts of cholic acid. CDCA concentrations varied between 62 and 2990 mg per kg dry weight, and the highest concentrations were found in two samples from fresh chicken manure, confirming that chickens can produce high but varying amounts of faecal CDCA. As a proof of principle, a newly created Pseudomonas putida KT2440 strain expressing a heterologous 7α−/7β‐hydroxysteroid dehydrogenase system was shown to be able to transform manure‐derived CDCA into UDCA without prior substrate purification from raw ethanolic chicken manure extracts. These results demonstrate that chicken manure can be used as an untapped resource for bile acids for biotechnological applications, providing a novel approach for the valorisation of this bioresource.